Art, philosophy and the question of good life - Wolf, Ursula; Santos-Ihlau, Rosa Helena (Estudios de Filosofía, 1995)
This essay deals in the first case with the identification of those questions and themes that are incumbent to aesthetics; secondly it broaches the issue ofthe latter’s relevance within the scope of philosophical reflection; thirdly and finally it tackles the notion of whether such issues and themes may be treated by such procedure as pertaining to philosophy. The general intention as has been identified leads to the justification of aesthetics as an important field in philosophical research.